PERAN BUDAYA SEKOLAH DALAM MEMODERASI PENGARUH KOMITMEN, MOTIVASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA (Students' Journal of Economic and Management, 2012)
The purpose of this research was to examine the effect of job commitment on teacher performance, motivation to work on teacher performance, career development on teacher performance, the role of school culture in moderating influence on the performance of teachers' work commitment, the role of school culture in moderating influence of motivation on teacher performance, and the role of school culture in moderating influence on the career development of teacher performance. This research sampled 125 respondents consisting of junior high school’s teachers in sub-rayon 05 Semarang. The test of hypothesis proposed in this model used regression analysis techniques moderation with an absolute difference. Results showed a significant effect between work commitment and motivation on teacher performance. While there is no significant influence on the career development of teacher performance. The role of school culture moderating only on the relationship between career development with teacher performance, while the relationship between performance and commitment to work with the relationship between motivation and performance, strengthening school culture has no role or not moderate.Key words: work commitment, motivation, career development, school culture, teacher performance.